External Comparator Cohort studies - clarification of terminology - Rippin, Gerd; Largent, Joan; Hoogendoorn, Wilhelmina Elisabeth; Sanz, Héctor; Bosco, Jaclyn; Mack, Christina (Frontiers in Drug Safety and Regulation, 2024)
Though there is only one term for the gold standard of Randomized Controlled Trials the terminology used for controlled research involving external data is diverse. Common terms include External Comparator/Control Arm study, Externally Controlled Trial, Synthetic Control study and Historical Control study. The term Externally Controlled Trial was recently selected by the U.S. Food and Drug Administration (FDA) and is in line with the use case of a pivotal trial. It entails pre-specification of the external dataset and its analysis in the trial protocol, which produces the highest amount of transparency, which is an important aspect for maximum credibility. If this pre-specification did not occur, we advocate the term External Comparator Cohort study (or short External Comparator study), which is derived by scrutinizing the paired terms study/trial, control/comparator and arm/cohort. Furthermore, we propose an overall framework of nomenclature, which is generally applicable for research projects involving external data. Only a precise and consistent use of terminology will most effectively safeguard from unintended implications, inaccurate perceptions, and misguided mindsets.